PENGARUH TINGKAT PENDIDIKAN GURU, BEASISWA PENDIDIKAN DAN FASILITAS SEKOLAH TERHADAP PRODUKTIVITAS KERJA GURU PADA MADRASAH IBTIDAIYAH ALMUTTAQIN TANJUNG TRITIP LUBUK BAJA KOTA BATAM - Sabri Sabri (Universitas Riau Kepulauan, 2016)
Human resources play an important role in determining the success of an organization. Urian the author to convey in general can be summarized as follows: In testing the hypothesis whether the variables education level influence on Work Productivity, then Because t arithmetic (6.010) t table (1.697), then Ho is rejected and H1 accepted, meaning; Significant regression coefficient or a variable effect on the education level Work Productivity, In testing the hypothesis variable Scholarship Award for Educational influence on Work Productivity, then Because t arithmetic (5.067) t table (1.697), then Ho is rejected and H1 accepted, meaning; Significant regression coefficients or variables affect the variable Scholarship Work Productivity, In testing the hypothesis whether variables affect the School Facilities Work Productivity, then Because t arithmetic (4.294) t table (1.697), then Ho is rejected and H1 accepted, meaning; Significant regression coefficient or a variable effect on the School Facilities Work Productivity variable, In testing the hypothesis whether the variable Level of Education, Scholarship and School Facilities simultaneously affect the Work Productivity. Anova gives the figure of 11,908 F count F table with a significance level of 2.93 (probability figure) of 0.05. F count F table then Ho is rejected and H1 accepted. Then the regression coefficient Level of Education, provision of scholarships Education and School Facility jointly significant effect on Work Productivity variables.